Anticonvulsant effect of gentamicin on the seizures induced by kainic acid. (2nd January 2018) - Zhao, Yuxiao; Wang, Ziyi; Lao, Wenwen; Kuang, Ping; Jiang, Nan; Yin, Tao; Lin, Weide; Zhu, Hongyan; Ji, Yonghua
Abstract: Objective:  Epilepsy is a chronic neurological disorder affecting approximately 0.5–2% of the population worldwide. Gentamicin (GM) is an aminoglycoside antibiotic used to treat several types of bacterial infections. We investigate whether the administration of GM can reduce seizures in temporal lobe epilepsy (TLE). Methods: The animal model of temporal lobe epilepsy (TLE) was established by kainic acid (KA) intrahippocampal injection. Behavioral test and Electroencephalography (EEG) recordings were performed to detect the effects of GM on the seizures triggered by KA injection in rats. Furthermore, immunofluorescence was used to investigate the influence of GM on the c-fos expression in the hippocampus. Results:  Here we found that the intracerebroventricular administration of GM is able to prevent the seizures induced by intrahippocampal kainic acid (KA) injection. Behaviorally, the latent period to the first seizure was significantly prolonged by GM. GM can totally abolish the occurrence of stage IV or V seizures and prominently reduce the total seizure duration. Electrographic recording showed that the latent period to the first seizure, the number and duration of high-amplitude, high-frequency discharges were remarkably reduced by GM. Additionally, the expression of c-fos was significantly decreased in the ipsilateral hippocampus of KA-injected rats treated with GM compared with KA-injected rats treated with saline. Conclusion:  These findings could promote the understanding of the pharmacological effects of GM, enriching the application of gentamicin in clinical practice.